Translational Highlights in Breast and Ovarian Cancer 2019 – Immunotherapy, DNA Repair, PI3K Inhibition and CDK4/6 Therapy - Hartkopf, Andreas D.; Müller, Volkmar; Wöckel, Achim; Lux, Michael P.; Janni, Wolfgang; Ettl, Johannes; Belleville, Erik; Schütz, Florian; Fasching, Peter A.; Kolberg, Hans-Christian; Welslau, Manfred; Overkamp, Friedrich; Taran, Florin-Andrei; Brucker, Sara Y.; Wallwiener, Markus; Tesch, Hans; Fehm, Tanja N.; Schneeweiss, Andreas; Lüftner, Diana (Geburtshilfe und Frauenheilkunde, 2019)
In the near future, important translational questions of clinical relevance will be adressed by studies currently in progress. On the one hand, the role of PD-L1 expression must be further understood, after it was found to be relevant in the use of atezolizumab in first-line therapy of patients with metastatic triple-negative breast cancer (TNBC). No association between efficacy and PD-L1 expression was found in a neoadjuvant study that included pembrolizumab in TNBC. The pathological complete response rate (pCR) was higher in both patient groups with and without PD-L1 expression when pembrolizumab was added to chemotherapy. Another future question is the identification of further patient groups in which efficacy of PARP inhibitors is seen, which are licensed for the pBRCA1/2 germline mutation. These include, for example, patients with mutations in other genes, which are involved in homologous recombination, or patients with tumours that show an abnormality in global tests of homologous recombination deficiencies (HRD tests). The question of whether a PARP inhibitor can be given and with which chemotherapy combination partners is currently being investigated in both breast and ovarian cancer. While the data on improved overall survival are being consolidated for the CDK4/6 inhibitors, knowledge of molecular changes during the therapy and during progression on the therapy is growing. Both the accumulation of PI3K mutations and also PTEN changes might play a part in planning subsequent therapies. This review article summarises these recent developments in breast cancer and in part also in ovarian cancer.Im Rahmen von aktuell laufenden Studien werden in naher Zukunft wichtige translationale Fragestellungen von klinischer Relevanz geklärt werden. Zum einen muss die Rolle der PD-L1-Expression, nachdem sie für die Indikationsstellung für Atezolizumab in der 1. Therapielinie bei Patientinnen mit einem metastasierten triple-negativen Mammakarzinom (TNBC) von Relevanz ist, weiter geklärt werden. In einer neoadjuvanten Studie beim TNBC mit Pembrolizumab konnte kein Zusammenhang zwischen Wirksamkeit und PD-L1-Expression gefunden werden. Sowohl mit als auch ohne Expression war die pCR höher, wenn Pembrolizumab zur Chemotherapie hinzugefügt wurde. Des Weiteren wird für die bei Keimbahnmutation von BRCA1/2 zugelassenen PARP-Inhibitoren nach weiteren Patientengruppen gesucht, in denen eine Wirksamkeit besteht. Dieses sind z. B. Patientinnen mit Mutationen in anderen Genen, die an der homologen Rekombination beteiligt sind, oder Patientinnen mit Tumoren, die bei globalen Tests zu homologen Rekombinationsdefizienzen (HRD-Tests) eine Auffälligkeit zeigen. Auch die Frage, ob und mit welchen Chemotherapie-Kombinationspartnern eine PARP-Inhibition zusammen gegeben werden kann, wird aktuell sowohl beim Mamma- als auch beim Ovarialkarzinom untersucht. Während sich die Daten zum verbesserten Gesamtüberleben bei den CDK4/6-Inhibitoren konsolidieren, wächst auch das Wissen um molekulare Veränderungen unter der Therapie und bei der Progression unter der Therapie. Sowohl die Anhäufung von PI3K-Mutationen als auch PTEN-Veränderungen könnten bei der Planung von Folgetherapien eine Rolle spielen. Diese Übersichtsarbeit fasst diese aktuellen Entwicklungen beim Mammakarzinom und teilweise auch beim Ovarialkarzinom zusammen.
Keywords: advanced breast cancer; metastases; therapy; mutation testing; immunotherapy; PARP; CDK4/6; BRCA1/2; PD-L1